Síntese e caracterização da ferrita de MnZn obtida pelo método dos citratos precursores - Bezerra, Maria José Oliveira da Silva (2007)
It was synthesized MnZn ferrite with general formulae Mn1-xZnxFe2O4 (mol%), 0,3 ≤ x ≤ 0,7 by using the citrate precursor method. The precursors decomposition was studied by thermogravimetric analysis (TGA), differential thermogravimetric analysis (DTG), differential thermal analysis (DTA) and Fourier transform infrared (FTIR) of powder calcined at 350ºC/3,5h. X-ray diffraction pattern (XRD) of samples was done from 350 to 1200ºC/2h using various atmospheres. The power calcined at 350ºC/3,5h formed spinel phase. It is necessary atmosphere control to avoid secondary phase such as hematite. From 900 to 1200ºC was obtained 90,66 and 100% of MnZn spinel ferrite phase, respectively. Analysis by dispersive energy scanning (EDS) at 350ºC shows high Mn and Zn dispersion, indicating that the diffusion process was homogeneous. Semi-quantitative analysis by EDS verified that despite the atmosphere control during calcinations at high temperatures (< 800ºC) occurred ZnO evaporation causing stoichiometric deviation. Vibrating sample magnetometer (VSM) measures show soft ferrite material characteristics with Hc from 6,5 x 10-3 to 11,1 x 10-2 T. Saturation magnetization (Ms) and initial permeability (µi) of MnZn spinel phase obtained, respectively, from 14,3 to 83,8 Am2/kg and 14,1 to 62,7 (Am2/kg)T